2015
DOI: 10.1002/hyp.10428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of differing coverage of moss-dominated soil crusts on hydrological processes and implications for disturbance in the Mu Us Sandland, China

Abstract: Abstract:To study the effects of biological soil crusts (BSCs) on hydrological processes and their implications for disturbance in the Mu Us Sandland, the water infiltration, evaporation and soil moisture of high coverage (100% BSCs), middle coverage (40% BSCs) and low coverage (0% BSCs, bare sand) of moss-dominated crusts were conducted in this study, respectively. The conclusions are as follows: (1) the main effects of moss-dominated crusts in the Mu Us Sandland on the infiltration of rainwater were to reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…The variability of the hydrological and erosion response with biological soil crusts depended on the crust composition, the underlying material properties and the stage of crust development (Kideon and Yair, 1997;Cantón et al, 2001;Rodríguez-Caballero et al, 2012). The biological crusts protected the topsoil directly exposed to the raindrops, and the lichen and moss growing on the topsoil improved the soil structure (Leys and Eldridge, 1998;Malam Issa et al, 2001;Jordán et al, 2010) and provided a certain strength that was useful in against concentrated flow scouring (Knapen et al, 2007;Yang et al, 2015). The development of surface crust encouraged runoff, but it also produced a soil surface that had a greater resistance to detachment (Janeau et al, 2003;Kinnell, 2005).…”
Section: Effects Of Land Cover Type On Red Soil Erosionmentioning
confidence: 99%
“…The variability of the hydrological and erosion response with biological soil crusts depended on the crust composition, the underlying material properties and the stage of crust development (Kideon and Yair, 1997;Cantón et al, 2001;Rodríguez-Caballero et al, 2012). The biological crusts protected the topsoil directly exposed to the raindrops, and the lichen and moss growing on the topsoil improved the soil structure (Leys and Eldridge, 1998;Malam Issa et al, 2001;Jordán et al, 2010) and provided a certain strength that was useful in against concentrated flow scouring (Knapen et al, 2007;Yang et al, 2015). The development of surface crust encouraged runoff, but it also produced a soil surface that had a greater resistance to detachment (Janeau et al, 2003;Kinnell, 2005).…”
Section: Effects Of Land Cover Type On Red Soil Erosionmentioning
confidence: 99%
“…Previous studies demonstrated that dry sand layers and BSCs could effectively restrict the soil evaporation rate (Z. Wang et al, 2006;Lv et al, 2006;Liu et al, 2006;Dong et al, 1999;Yang et al, 2015;Fu et al, 2010;Liu, 2012). However, the bulldozing of sand dunes at our experimental site made the elevation of the flat soil surface lower than the average elevation of the undisturbed soil surface (approximately 1.5 m lower, Fig.…”
Section: Possible Reasons For the Effects Of Land Use/cover Changesmentioning
confidence: 99%
“…The area covers only 40 000 km 2 (Dong and Zhang, 2001) and is ecologically fragile (Yang et al, 2007). In such an ecosystem, sand dunes and BSCs are commonly observed (Gao et al, 2014;Yang et al, 2015;Li and Li, 2000;Liu, 2012). Due to the existence of BSCs and dry sand layers (Z.…”
mentioning
confidence: 99%
“…During the entire infiltration process, water temperature was monitored with mercurial thermometer. The infiltration rate and cumulative infiltration were calculated for the equation (Yang et al, 2015).…”
Section: Methodsmentioning
confidence: 99%